Кинетика деформации ВАХ оксидных варисторных структур, обусловленная перезарядкой локализованных состояний - Tonkoshkur, A. S.; Ivanchenko, A. V. (PE "Politekhperiodika", Book and Journal Publishers, 2014)
Prolonged exposure of zinc oxide varistors to the electrical load leads to current-voltage characteristics (CVC) deformation, which is associated with a change in the height and width of the intergranular barriers, which are the main structural element of the varistors. Polarization phenomena in zinc oxide ceramics are studied in a number of works, but those are mainly limited to the study of the physics of the CVC deformation process and to determining the parameters of localized electronic states involved in this process. This paper presents the results on the simulation of the deformation of pulse CVC of a separate intergranular potential barrier at transient polarization/depolarization, associated with recharging of surface electronic states (SES), which cause this barrier. It is found that at high density of SES their degree of electron filling is small and the effect of DC voltage leads to a shift of pulse current-voltage characteristics into the region of small currents. Conversely, the low density SES are almost completely filled with electrons, and after crystallite polarization CVC is shifted to high currents. Experimental studies have confirmed the possibility of applying the discovered laws to ceramic varistor structures. The proposed model allows interpreting the «anomalous» effects (such as increase in the classification voltage and reduction of active losses power) observed during the varistors accelerated ageing test.